Assessing the United Nations' Capacity to Address Genocide Allegations in Gaza: A Critical Analysis of Institutional Constraints and Diplomatic Failures - Asep Setiawan (Asian Journal of Multidisciplinary Research, 2025)
This article critically evaluates the capacity of the United Nations (UN) to respond to genocide allegations in the Gaza Strip during the 2023–2025 period. Amid escalating civilian casualties, systemic infrastructure destruction, and diplomatic polarization, the UN's performance has come under scrutiny for its apparent institutional paralysis and failure to uphold its core mandate under the Genocide Convention and the Responsibility to Protect (R2P) doctrine. Through a qualitative analysis of peer-reviewed literature, UN records, and secondary legal data, this study uncovers three interlocking causes of failure: (1) structural limitations of the Security Council, especially the abuse of veto power by permanent members; (2) selective humanitarianism and geopolitical bias that shape legal interpretation and operational prioritization; and (3) institutional dissonance between fact-finding bodies and enforcement arms within the UN system. The results show that the UN's fragmented and inconsistent response to the Gaza crisis undermines the legitimacy of international legal norms, particularly when compared with its swift and unified response to the war in Ukraine. The study also introduces two novel conceptual tools—procedural latency and diplomatic shielding—to describe the bureaucratic and political mechanisms that inhibit timely action. Policy recommendations include structural reforms to the veto system, enhanced integration between the UNHRC and ICC, and the decentralization of atrocity verification. Without these changes, the UN risks further erosion of its normative authority and global relevance. The Gaza case thus serves as a sobering diagnostic of institutional failure—and an urgent call for global governance reform.